Broadband interference filters with suppression of high reflection bands of 4-, 5- and 6-th orders - Pervak, V.Yu.; Poperenko, L.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2005)
The influence of optical constants dispersion on spectral properties of multilayer interference systems, in which spectral characteristics suppression of the adjacent bands of high reflection of 4, 5 and 6-th orders are observed, is investigated. Examples of realization of synthesized interference filters are resulted and features of their manufacturing are considered.